A constitution for the European Union - Blankart, Charles Beat; Mueller, Dennis C. (MIT Press, 2004)
International economists and other scholars address the major issues that arise in writing a European constitution, including the evolution of federalism and the role of direct democracy. The leaders of European Union member states have declared that a European constitution should take "a clear, open, effective, democratically controlled Community approach." Their goal--that within the Union, "European institutions should be brought closer to its citizens"--Raises many questions about implementation. What is the most effective procedure for connecting citizens' preferences to political action and policy choices at the EU level? The contributors to this CESifo volume, internationally prominent economists and other scholars, address the major issues that arise in the writing of a constitution. They do so with the underlying assumption that individuals are rational actors and the goal of the state is to advance their collective interests. The ten chapters consider such topics as how a constitution might be designed to prevent military conflict, whether the EU will evolve "by default" into a federal state, the apparent contradiction between the evolutionary development of the EU and the static structure of the constitution, the definition of citizenship and rights, the division and distribution of power, the budgetary deadlock on the provision of public goods and the redistribution of resources, coordinating policy, alternative methods for choosing an EU president, and the role of such direct democracy institutions as referenda and initiatives. The editors conclude by summing up the main arguments advanced to offer a unified sapproach to these issues
Keywords: European Union.; European Union; Constitutional law -- European Union countries.; Droit constitutionnel -- Pays de l'Union européenne.; LAW -- Constitutional.; LAW -- Public.; Constitutional law; European Union countries; ECONOMICS/International Economics; ECONOMICS/Political Economy